2020
DOI: 10.1111/tog.12670
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations of pregnancy and labour: from the innocuous to the sight threatening

Abstract: Pregnancy may precipitate several physiological changes that can have ocular consequences; many of these are innocuous and require little more than reassurance for the patient. There are uncommon instances of new sight-threatening pathology that necessitate a prompt approach. Pregnant women presenting to the ophthalmologist with ocular symptoms can cause concern because alternative differentials may need to be considered; and the potential teratogenic or fetotoxic effects of investigations or treatment mean th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
5
0
1
Order By: Relevance
“…Notably, antiglaucoma medications carry teratogenic risks and are contraindicated for pregnant women. Therefore, laser trabeculoplasty is recommended as a means to manage intraocular pressure before a glaucoma patient plans pregnancy [14][15][16][17][18].…”
Section: Brief Review Of Eye Disease In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, antiglaucoma medications carry teratogenic risks and are contraindicated for pregnant women. Therefore, laser trabeculoplasty is recommended as a means to manage intraocular pressure before a glaucoma patient plans pregnancy [14][15][16][17][18].…”
Section: Brief Review Of Eye Disease In Pregnancymentioning
confidence: 99%
“…Common symptoms include headaches and vision disturbances, such as transient visual obscuration, visual field loss, and reduced central visual acuity. Due to the thrombotic risk associated with pregnancy, imaging is urgently required to exclude cerebral venous sinus thrombosis, which will be expanded on below [18,19,25].…”
Section: Papilledema and Pregnancymentioning
confidence: 99%
“…Prior survey studies reported that some obstetricians advocate for assisted delivery via cesarean section or instrumental delivery instead of spontaneous vaginal delivery for patients who have a history of RRD repair [2,3]. However, several studies in the literature suggest that no correlation exists between RD and labor or spontaneous vaginal delivery [4][5][6][7].…”
Section: Retinal Detachment and Childbirthmentioning
confidence: 99%
“…Proliferatív diabeteses retinopathiában (C) a papilla területében szabálytalan, kóros érújdonképződések jelennek meg (fekete nyilak). A D ábra a szemfenéki lézerkezelés elvégzése után a periférián látható pigmentá lódó lézergócokat ábrázolja kontrakciója esetén indikált, ha a trakciós retinaleválás a centrális látást veszélyezteti [25].…”
Section: áBraunclassified